posted by Valerie .
Can someone please help me do this problem? That would be great!
Simplify the expression:
sin theta + cos theta * cot theta
I'll use A for theta.
Cot A = sin A / cos A
sin A + (cos A * sin A / cos A) =
sin A + sin A =
2 sin A
I hope this will help.
in my algebra book, it says that Cot A=cos A/sin A, not sin A/cos A
That changes things a bit, doesn't it?
cot A = cos A / sin A
sin^2 A + cos^2 A = 1
sin A + (cos A * cos A / sin A) =
sin A + (cos^2A / sin A) =
Using sin A as a common denominator:
(sin^2 A / sin A) + (cos^2 A / sin A) =
(sin^2 A + cos^2 A) / sin A =
1 / sin A
Sorry for the error.